2007
DOI: 10.1002/jbm.b.30900
|View full text |Cite
|
Sign up to set email alerts
|

Hardness and elastic modulus of TiO2 anodic films measured by instrumented indentation

Abstract: The aim of this work was to investigate the mechanical properties of the titanium anodic films (TiO2) produced by anodic oxidation under galvanostatic conditions, using a 1.4M phosphoric acid electrolyte, with different current densities (J) on commercially pure titanium (cp-Ti). The morphology of the oxide films were observed by scanning electron microscopy (SEM), whereas the composition of the film was determined by Raman spectroscopy. Porosity, average roughness (Ra) and thickness of the TiO2 films increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 58 publications
(132 reference statements)
8
41
0
Order By: Relevance
“…Besides, yield strength is usually determined by its linear relationship with hardness, which we aim to determine in the present work. Soares et al (2008) suggested a relation between yield strength and plasticity index, however, it is valid only for rigid surfaces such as ceramic oxides. Since Kim et al (1997b) reported that the film thickness increases with the alkali treatment period, we employed an alternative method using a thicker film produced by alkali treatment for 72 h and regular heat treatment (AHT-72).…”
Section: Fig 4 -Elastic Modulus Profiles Of Ti Surfaces Submitted Tomentioning
confidence: 97%
“…Besides, yield strength is usually determined by its linear relationship with hardness, which we aim to determine in the present work. Soares et al (2008) suggested a relation between yield strength and plasticity index, however, it is valid only for rigid surfaces such as ceramic oxides. Since Kim et al (1997b) reported that the film thickness increases with the alkali treatment period, we employed an alternative method using a thicker film produced by alkali treatment for 72 h and regular heat treatment (AHT-72).…”
Section: Fig 4 -Elastic Modulus Profiles Of Ti Surfaces Submitted Tomentioning
confidence: 97%
“…The index f indicates the layer and s indicates the substrate. The above equation is valid for the situation where the layer is harder than the substrate, which is applicable in anodic layers (Santos Jr. et al, 2007;Soares et al, 2008). The Bhattacharya and Nix model has been presented as a satisfactory choice to obtain the layer hardness (Fischer-Cripps, 2004 Since the layer hardness is the concern of this study, a different approach is needed for the layer yield strength Y f .…”
Section: Hardnessmentioning
confidence: 97%
“…The Poisson's ratio for Ti is well known (ν = 0.32). For the titania layers it was assumed that ν = 0.28 (Soares et al, 2008). Calculations were performed for all points constituting the composite profiles, since they lay inside the layer region (depths up to 3 µm).…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the bioceramic coatings and calcium orthophosphates in particular, applied on Ti-based substrates, having a useful combination of biocompatibility, mechanical properties and relative stability in bodily environment, are subjects of an increasing interest for biomedical applications in modern orthopaedics and dentistry (Gaona et al, 2007;Salman et al, 2008;Soares et al, 2008;Thomas, 1994).…”
Section: Ti-based Implants With Bioceramic Coatingsmentioning
confidence: 99%